Extrato de Bauhinia variegata possui efeito tipo-antidepressivo em camundongos com envolvimento do sistema monoaminérgico - Schöffer, Ana Paula (2015)
Depression is a psychiatric disorder that affects 2-15% of the world population. It is a heterogeneous neuropathology, it includes psychological, behavioral and physiological symptoms. Despite having several treatments for depression, they are not as effective and have many undesirable side effects. Therefore, it is necessary the development of new therapeutic strategies to improve current treatments. Therefore, open up doors to the use of plant medicines, which has already been used for thousands of years by various populations for different diseases. The Bauhinia variegata, popularly known as "pata-de-vaca", has beneficial health effects, such as anti-inflammatory activity, antidiabetic, antidiarrheal. In the present study, we investigated the antidepressant-like effect of the crude hydroethanolic extract of leaves of Bauhinia variegata in two predictive tests of antidepressant property, the tail suspension test (TST) and the forced swimming test (FST) in mice. Furthermore, the involvement of monoaminergic system in its antidepressant-like effect was investigated and the effect of extract on monoamine oxidase A (MAO-A) activity was also evaluated. The acute treatment with the extract of Bauhinia variegate (300 mg/kg, p.o.) significantly reduced the immobility time in the TST. Moreover, the repeated administration (once a day for 7 days) of the extract by p.o. route also produced an antidepressant-like effect in the TST (100 and 300 mg/kg) and FST (300 mg/kg).The pretreatment of mice with ketanserin (5 mg/kg, i.p. a preferential 5-HT2A receptor antagonist), prazosin (1 mg/kg, i.p. an α1-adrenoceptor antagonist), yohimbine (1 mg/kg, i.p. an α2-adrenoceptor antagonist), propranolol (2 mg/kg, i.p. a β-adrenoceptor antagonist), SCH23390 (0.05 mg/kg, i.p. a dopamine D1 receptor antagonist) or sulpiride (50 mg/kg, i.p. a dopamine D2 receptor antagonist) was able to reverse the anti-immobility effect of the extract (300 mg/kg, p.o) in TST. The combination of subeffective dose of fluoxetine (5 mg/kg, p.o.), imipramine (5 mg/kg, v.o.) or bupropion (5 mg/kg, v.o.) with a subffective dose of the extract (100 mg/kg) produced a synergistic antidepressant-like effect in the TST. The extract did not cause motor alteration in the open-field test at effective doses in both TST and FST. We also showed that the extract inhibited the MAO-A activity of mice brain in vitro. These results suggest that the extract from Bauhinia variegata present an antidepressanloke potential, which may be dependent on the monoaminergic system and its MAO-A inhibitory properties.